Skip-beat!. 40 - Nakamura, Yoshiki; Kimura, Tomo (Shojo beat manga., 2018)
"Kyoko Mogami followed her true love Sho to Tokyo to support him while he made it big as an idol. But he's casting her out now that he's famous! Kyoko won't suffer in silence--she's going to get her sweet revenge by beating Sho in show biz! Kyoko desperately wants to be cast in a new samurai drama so that she can work opposite her best friend in the entire world, Kanae "Moko" Kotonami. But there are plenty of hurdles between her and her dream role, including another actress who might be willing to do anything to take out the competition!"--pg.4 of cover.